Packaging materials and batteries

JP7652667B2Active Publication Date: 2025-03-27DAI NIPPON PRINTING CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021145434
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-01-29
Filing Date
2021-09-07
Publication Date
2025-03-27
Estimated Expiration
2037-01-27

Smart Images

  • Figure 0007652667000006
    Figure 0007652667000006
  • Figure 0007652667000007
    Figure 0007652667000007
  • Figure 0007652667000008
    Figure 0007652667000008
Patent Text Reader

Abstract

To provide a packaging material having excellent impact resistance.SOLUTION: A packaging material is composed of a laminate having at least a base material layer, a barrier layer, and a heat-sealing resin layer in this order, and in the laminate, the breaking energy per unit width of 1 m calculated from the curve of test force-displacement amount measured when the tensile test is performed under the following test conditions is 400 J or more in total of one direction which is the vertical direction to the thickness direction of the laminate and the other directions which is vertical direction to the one direction and the thickness direction of the laminate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to packaging materials and batteries. [Background technology]

[0002] Conventionally, packaging materials for packaging contents have been widely used in the fields of food, medicine, etc. As such packaging materials, film-like laminates in which a substrate, a barrier layer, and a heat-sealable resin layer are laminated in this order are known, and the contents can be sealed by heat-sealing the heat-sealable resin layers together.

[0003] In recent years, with the increasing performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc., batteries are required to have a variety of shapes, as well as to be thin and lightweight. However, the metal packaging materials that have been widely used in the past have the disadvantage that it is difficult to keep up with the diversification of shapes, and there is also a limit to how much weight can be reduced. Therefore, in the field of batteries, a film-like laminate in which a substrate / barrier layer / thermally adhesive resin layer are laminated in this order has been proposed as a packaging material that can be easily processed into a variety of shapes and can achieve a thin and lightweight structure, instead of a metal packaging material (Patent Document 1).

[0004] These various packaging materials are sometimes subjected to strong external impacts during transportation, etc., and therefore are required to have high impact resistance. On the other hand, in recent years, from the viewpoint of making products thinner and lighter, there has been a demand for packaging materials to be made even thinner. However, as the thickness of packaging materials decreases, there is a problem that impact resistance decreases. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-287971 A Summary of the Invention [Problem to be solved by the invention]

[0006] A primary object of the present invention is to provide a packaging material having excellent impact resistance, the packaging material being a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. [Means for solving the problem]

[0007] The present inventors have conducted intensive studies to solve the above problems. As a result, they have found that a packaging material consisting of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order has excellent impact resistance when the breaking energy per unit width of 1 m calculated from a curve of "test force-displacement" measured when a tensile test is performed on the laminate under the following test conditions is 400 J or more in total in one direction perpendicular to the thickness direction of the laminate and in another direction perpendicular to both the one direction and the thickness direction of the laminate. The present invention has been completed based on these findings and through further studies. (Test conditions) Test speed: 50mm / min Test piece width: 15mm Test piece length: 100mm Gauge distance: 30mm

[0008] That is, the present invention provides a packaging material and a battery having the following aspects. Item 1. The laminate is made of at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The laminate has a breaking energy per unit width of 1 m, calculated from a test force-displacement curve measured when a tensile test is performed under the test conditions described below, of 400 J or more in total in one direction perpendicular to the thickness direction of the laminate and in another direction perpendicular to both the one direction and the thickness direction of the laminate. (Test conditions) Test speed: 50mm / min Test piece width: 15mm Test piece length: 100mm Gauge distance: 30mm Item 2. The packaging material according to item 1, wherein the one direction is the MD of the laminate and the other direction is the TD of the laminate. Item 3. The packaging material according to item 1 or 2, wherein the laminate has a puncture strength of 23 N or more as measured from the base layer side by a method conforming to the provisions of JIS Z1707:1995. Item 4. The packaging material according to any one of Items 1 to 3, wherein the laminate has a total penetration energy of 1.4 J or more measured from the base layer side in accordance with JIS K7124-2:1999 under the following measurement conditions: (Measurement conditions) Hammer weight: 6.4kg Drop height: 300mm Sample clamp diameter: 40mmφ Hammer diameter: 12.7mm Hammer Shape: Hemispherical Item 5. The packaging material according to any one of Items 1 to 4, wherein the base layer has a thickness of 20 μm or more. Item 6. The packaging material according to any one of Items 1 to 5, wherein the barrier layer is made of aluminum foil. Item 7. The packaging material according to any one of Items 1 to 6, which is used to house a battery element. Item 8. A battery, comprising a battery element including at least a positive electrode, a negative electrode, and an electrolyte, housed in a package formed from the packaging material according to any one of Items 1 to 7. Effect of the Invention

[0009] According to the present invention, in a packaging material consisting of a laminate having at least a base material layer, a barrier layer, and a heat-sealable resin layer in this order, the breaking energy per unit width of 1 m, calculated from the "test force-displacement amount" curve measured when a tensile test is performed on the laminate under the test conditions described above, is 400 J or more in total in one direction perpendicular to the thickness direction of the laminate and in another direction perpendicular to both the one direction and the thickness direction of the laminate, thereby providing a packaging material with excellent impact resistance. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a diagram showing an example of a cross-sectional structure of a packaging material of the present invention. [Diagram 2] FIG. 1 is a diagram showing an example of a cross-sectional structure of a packaging material of the present invention. [Diagram 3] FIG. 1 is a diagram showing an example of a cross-sectional structure of a packaging material of the present invention. [Figure 4] 1 is a curve (MD) of test force versus displacement obtained in a tensile test of the packaging material of Comparative Example 2. [Diagram 5] FIG. 1 is a schematic diagram showing a portion where data on a test force-displacement curve is integrated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The packaging material of the present invention is composed of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, and the laminate is characterized in that the breaking energy per unit width of 1 m, calculated from a test force-displacement curve measured when a tensile test is performed under the following test conditions, is 400 J or more in total in one direction perpendicular to the thickness direction of the laminate and in another direction perpendicular to both the one direction and the thickness direction of the laminate. The packaging material of the present invention will be described in detail below. (Test conditions) Test speed: 50mm / min Test piece width: 15mm Test piece length: 100mm Gauge distance: 30mm

[0012] In this specification, the numerical range indicated by "to" means "greater than or equal to" or "less than or equal to." For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.

[0013] 1.Layer structure and physical properties of packaging materials The packaging material of the present invention is composed of a laminate in which at least a base material layer 1, a barrier layer 3, and a heat-sealable resin layer 4 are laminated in this order, as shown in Fig. 1. In the packaging material of the present invention, the base material layer 1 is the outermost layer, and the heat-sealable resin layer 4 is the innermost layer. That is, when assembling a battery, the heat-sealable resin layers 4 located on the periphery of the battery element are heat-sealed to each other to seal the battery element, thereby sealing the battery element.

[0014] In the packaging material of the present invention, for example, as shown in Fig. 2, an adhesive layer 2 may be provided between the base material layer 1 and the barrier layer 3, if necessary, for the purpose of enhancing adhesion therebetween. In addition, in the packaging material of the present invention, for example, as shown in Fig. 3, an adhesive layer 5 may be provided between the barrier layer 3 and the heat-fusible resin layer 4, if necessary, for the purpose of enhancing adhesion therebetween.

[0015] The laminate constituting the packaging material of the present invention has a breaking energy per unit width of 1 m calculated from a curve of "test force-displacement amount" measured when a tensile test is performed under the test conditions, the breaking energy being 400 J or more in one direction perpendicular to the thickness direction of the laminate (i.e., the stacking direction of the laminate) and the other direction perpendicular to the one direction and the thickness direction of the laminate (i.e., the other direction is perpendicular to the one direction and also perpendicular to the thickness direction of the laminate). From the viewpoint of improving the impact resistance while reducing the thickness of the packaging material, it is preferable that the one direction is the MD (machine direction) of the laminate and the other direction is the TD (transverse direction) of the laminate. That is, it is preferable that the breaking energy per unit width of 1 m calculated from a curve of "test force-displacement amount" measured when a tensile test is performed under the test conditions is 400 J or more in total in the MD, which is the flow direction of the laminate, and the TD, which is the perpendicular direction. In the present invention, the tensile test means a test of tensile properties.

[0016] From the viewpoint of improving impact resistance while reducing the thickness of the packaging material, the lower limit of the breaking energy is preferably about 450 J or more, more preferably about 500 J or more, and from the viewpoint of suitably forming the packaging material, the upper limit is about 1000 J or less, more preferably about 800 J or less. The range of the breaking energy is preferably about 400 to 1000 J, about 400 to 800 J, about 450 to 1000 J, about 450 to 800 J, about 500 to 1000 J, or about 500 to 800 J.

[0017] In addition, in the packaging material, the MD and TD of the barrier layer described later can usually be distinguished during the manufacturing process. For example, when the barrier layer is made of aluminum foil, linear streaks called rolling marks are formed on the surface of the aluminum foil in the rolling direction (RD) of the aluminum foil. Since the rolling marks extend along the rolling direction, the rolling direction of the aluminum foil can be grasped by observing the surface of the aluminum foil. In addition, in the manufacturing process of the laminate, the MD of the laminate usually coincides with the RD of the aluminum foil, so the MD of the laminate can be identified by observing the surface of the aluminum foil of the laminate and identifying the rolling direction (RD) of the aluminum foil. In addition, since the TD of the laminate is perpendicular to the MD of the laminate, the TD of the laminate can also be identified.

[0018] In the present invention, the breaking energy per 1 m of unit width in the one direction and the other direction of the laminate constituting the packaging material is calculated by acquiring data of the test force-displacement curve measured when performing a tensile test under the test conditions for the one direction and the other direction of the laminate, saving the data in a CSV file format, and integrating the data until the laminate breaks using a spreadsheet software (Microsoft Excel (registered trademark)). At this time, the breaking energy per 1 m width of each packaging material is converted (divided by 0.015) by the spreadsheet software and calculated. Then, the breaking energy per 1 m of unit width in the one direction and the breaking energy per 1 m of unit width in the other direction are summed up. Note that the time when the laminate breaks means the time when the test piece breaks. Note that five packaging materials are prepared for each measurement target, and the breaking energy values ​​for the five samples are averaged, for example, by the three values ​​excluding the maximum and minimum values, to be the breaking energy of the laminate. Even if five samples cannot be prepared, it is preferable to use the average measured with the number of samples that can be measured. In the tensile test, a commercially available tensile tester can be used.

[0019] From the viewpoint of improving impact resistance while reducing the thickness of the packaging material, the laminate constituting the packaging material of the present invention has a puncture strength measured from the base layer 1 side by a method conforming to the provisions of JIS Z1707:1995, of preferably about 23 N or more, more preferably about 24 N or more, and even more preferably about 26 N or more, and from the viewpoint of suitably forming the packaging material, the upper limit is preferably about 50 N or less, more preferably about 40 N or less. The puncture strength is preferably in the range of about 23 to 50 N, about 23 to 40 N, about 24 to 50 N, about 24 to 40 N, about 26 to 50 N, or about 26 to 40 N.

[0020] Furthermore, from the viewpoint of improving impact resistance while reducing the thickness of the packaging material, the laminate constituting the packaging material of the present invention preferably has a total puncture strength measured in accordance with the provisions of JIS Z1707:1995 for the substrate layer 1, barrier layer 3, and heat-sealable resin layer 4 described below of 23 N or more, preferably 23 to 50 N, and more preferably 23 to 40 N. When the laminate constituting the packaging material of the present invention has only the heat-sealable resin layer 4 disposed inside the barrier layer 3 as shown in Figs. 1 and 2, the puncture strength of the heat-sealable resin layer is a puncture strength measured only for the heat-sealable resin layer 4, whereas when the adhesive layer 5 and the heat-sealable resin layer 4 are disposed inside the barrier layer 3 as shown in Fig. 3 described below, the puncture strength is a puncture strength measured for the laminate of the adhesive layer 5 and the heat-sealable resin layer 4.

[0021] From the viewpoint of improving impact resistance while reducing the thickness of the packaging material, the laminate constituting the packaging material of the present invention conforms to the provisions of JIS K7124-2:1999 and the total penetration energy measured from the base layer 1 side under the following measurement conditions is preferably about 1.4 J or more, more preferably 1.5 J or more as a lower limit, and from the viewpoint of suitably forming the packaging material, is preferably 5.0 J or less, more preferably 4.5 J or less as an upper limit. The range of the total penetration energy is preferably about 1.4 to 5.0 J, about 1.4 to 4.5 J, about 1.5 to 5.0 J, or about 1.5 to 4.5 J.

[0022] (Measurement conditions) Hammer weight: 6.4kg Drop height: 300mm Sample clamp diameter: 40mmφ Hammer diameter: 12.7mm Hammer Shape: Hemispherical

[0023] The impact resistance of the packaging material of the present invention is evaluated, for example, by whether or not the packaging material breaks and the contents are exposed to the outside when a strong impact is applied from the outside while the heat-fusible resin layers 4 are heat-sealed to seal the contents. For example, in a battery sealed in a conventional metal can, the impact resistance is evaluated by a method conforming to the UL1642 standard. When the packaging material of the present invention is used, for example, to house a battery element (i.e., a battery packaging material), it is preferable that the packaging material passes the impact resistance evaluation by the method conforming to the UL1642 standard (no smoke, no fire, etc. occurs).

[0024] The thickness of the laminate constituting the packaging material of the present invention is not particularly limited, but from the viewpoint of making the thickness as thin as possible while ensuring excellent impact resistance, the upper limit is preferably about 160 μm or less, more preferably about 155 μm or less, and even more preferably about 120 μm or less, and the lower limit is preferably about 35 μm or more, more preferably about 45 μm or more. In addition, the range of the thickness of the laminate is preferably about 35 to 160 μm, about 35 to 155 μm, about 35 to 120 μm, about 45 to 160 μm, about 45 to 155 μm, and about 45 to 120 μm. Even when the thickness of the laminate constituting the packaging material of the present invention is thin, for example, about 160 μm or less, it can exhibit excellent impact resistance according to the present invention. Therefore, the packaging material of the present invention can contribute to improving the energy density of the battery.

[0025] 2. The layers that make up the packaging material [Base material layer 1] In the packaging material of the present invention, the base layer 1 is a layer located on the outermost layer side. The material forming the base layer 1 is not particularly limited as long as it has insulating properties. Examples of materials forming the base layer 1 include polyester, polyamide, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, phenolic resin, polyetherimide, polyimide, and mixtures and copolymers thereof.

[0026] Specific examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, polycarbonate, copolymerized polyesters mainly composed of ethylene terephthalate as a repeating unit, copolymerized polyesters mainly composed of butylene terephthalate as a repeating unit, etc. Specific examples of copolymerized polyesters mainly composed of ethylene terephthalate as a repeating unit include copolymerized polyesters mainly composed of ethylene terephthalate as a repeating unit and ethylene isophthalate (hereinafter abbreviated as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / isophthalate), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), polyethylene (terephthalate / decane dicarboxylate), etc. Specific examples of copolymer polyesters containing butylene terephthalate as the main repeating unit include copolymer polyesters in which butylene terephthalate as the main repeating unit is polymerized with butylene isophthalate (hereinafter abbreviated as polybutylene (terephthalate / isophthalate)), polybutylene (terephthalate / adipate), polybutylene (terephthalate / sebacate), polybutylene (terephthalate / decanedicarboxylate), polybutylene naphthalate, etc. These polyesters may be used alone or in combination of two or more. Polyesters have the advantage of being excellent in electrolyte resistance and being less likely to cause whitening or the like due to adhesion of electrolyte, and are therefore suitably used as materials for forming the base layer 1.

[0027] Specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and T represents terephthalic acid) containing structural units derived from terephthalic acid and / or isophthalic acid, and aromatic polyamides such as polymetaxylylene adipamide (MXD6); alicyclic polyamides such as polyaminomethylcyclohexyl adipamide (PACM6); polyamides copolymerized with lactam components and isocyanate components such as 4,4'-diphenylmethane-diisocyanate; polyesteramide copolymers and polyetheresteramide copolymers, which are copolymers of copolymerized polyamides with polyesters or polyalkylene ether glycols; and copolymers thereof. These polyamides may be used alone or in combination of two or more. A stretched polyamide film has excellent stretchability and can prevent whitening due to resin cracking of the base layer 1 during molding, and is therefore preferably used as a material for forming the base layer 1.

[0028] The substrate layer 1 may be formed of a uniaxially or biaxially stretched resin film, or may be formed of an unstretched resin film. Among them, a uniaxially or biaxially stretched resin film, particularly a biaxially stretched resin film, is preferably used as the substrate layer 1 because its heat resistance is improved by oriented crystallization. The substrate layer 1 may be formed by coating the barrier layer 3 with the above-mentioned material.

[0029] Among these, the resin film forming the base layer 1 is preferably nylon or polyester, more preferably biaxially oriented nylon or biaxially oriented polyester, and particularly preferably biaxially oriented nylon.

[0030] In order to improve pinhole resistance and insulation when used as a battery packaging material, the base layer 1 can be laminated (multilayer structure) with at least one of resin films and coatings made of different materials. Specifically, a multilayer structure in which a polyester film and a nylon film are laminated, a multilayer structure in which multiple nylon films are laminated, a multilayer structure in which multiple polyester films are laminated, etc. can be mentioned. When the base layer 1 has a multilayer structure, a laminate of a biaxially oriented nylon film and a biaxially oriented polyester film, a laminate in which multiple biaxially oriented nylon films are laminated, or a laminate in which multiple biaxially oriented polyester films are laminated is preferable. In addition, since biaxially oriented polyester is less likely to discolor when an electrolyte solution adheres to the surface, for example, when the base layer 1 has a multilayer structure of a laminate of a biaxially oriented nylon film and a biaxially oriented polyester film, the base layer 1 is preferably a laminate having biaxially oriented nylon and biaxially oriented polyester in this order from the barrier layer 3 side. When the base layer 1 has a multilayer structure, the thickness of each layer is preferably about 3 to 25 μm.

[0031] When the base material layer 1 has a multi-layer structure, each resin film may be bonded via an adhesive, or may be directly laminated without an adhesive. When bonding without an adhesive, for example, a method of bonding in a thermally molten state such as a co-extrusion method, a sandwich lamination method, or a thermal lamination method may be mentioned. When bonding via an adhesive, the adhesive used may be a two-component curing adhesive or a one-component curing adhesive. Furthermore, the bonding mechanism of the adhesive is not particularly limited, and may be any of a chemical reaction type, a solvent volatilization type, a thermal melting type, a thermal pressure type, an ultraviolet curing type, an electron beam curing type, and the like. Specific examples of the adhesive include the same adhesives as those exemplified in the adhesive layer 2. The thickness of the adhesive may also be the same as that of the adhesive layer 2.

[0032] In the present invention, from the viewpoint of improving the formability of the packaging material, it is preferable that a lubricant is attached to the surface of the base layer 1. The lubricant is not particularly limited, but preferably includes amide-based lubricants. Specific examples of amide-based lubricants include, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, and unsaturated fatty acid bisamides. Specific examples of saturated fatty acid amides include lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, and hydroxystearic acid amides. Specific examples of unsaturated fatty acid amides include oleic acid amides and erucic acid amides. Specific examples of substituted amides include N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, and N-stearyl erucic acid amides. Specific examples of methylol amides include methylol stearic acid amides. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, N,N'-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearamide ethyl stearate, etc. Specific examples of aromatic bisamides include m-xylylene bisstearic acid amide, m-xylylene bishydroxystearic acid amide, N,N'-distearylisophthalic acid amide, etc. The lubricant may be used alone or in combination of two or more kinds.

[0033] The content of the lubricant in the base layer 1 is not particularly limited, but from the viewpoint of improving the formability and insulating properties of the electronic packaging material, it is preferably about 0.01 to 0.2 mass %, more preferably about 0.05 to 0.15 mass %.

[0034] From the viewpoint of making the packaging material thin while having excellent impact resistance, the thickness of the base layer 1 is preferably about 10 μm or more, more preferably about 20 μm or more as the lower limit, and preferably about 75 μm or less, more preferably about 50 μm or less as the upper limit. The thickness of the base layer 1 is preferably in the range of about 10 to 75 μm, about 10 to 50 μm, about 20 to 75 μm, or about 20 to 50 μm. In the present invention, when the base layer 1 has a multilayer structure bonded with an adhesive, the thickness of the base layer 1 does not include the thickness of the adhesive.

[0035] [Adhesive layer 2] In the packaging material of the present invention, the adhesive layer 2 is a layer provided between the base material layer 1 and the barrier layer 3 in order to firmly bond them together.

[0036] The adhesive layer 2 is formed of an adhesive capable of bonding the base material layer 1 and the barrier layer 3. The adhesive used to form the adhesive layer 2 may be a two-component curing adhesive or a one-component curing adhesive. Furthermore, the adhesion mechanism of the adhesive used to form the adhesive layer 2 is not particularly limited, and may be any of a chemical reaction type, a solvent volatilization type, a thermal melting type, a thermal pressure type, and the like.

[0037] Specific examples of adhesive components that can be used to form the adhesive layer 2 include polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, polycarbonate, and copolymerized polyester; polyether-based adhesives; polyurethane-based adhesives; epoxy-based resins; phenol-based resins; polyamide-based resins such as nylon 6, nylon 66, nylon 12, and copolymerized polyamide; polyolefin-based resins such as polyolefin, carboxylic acid-modified polyolefin, and metal-modified polyolefin; polyvinyl acetate-based resins; cellulose-based adhesives; (meth)acrylic resins; polyimide-based resins; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; and silicone-based resins. These adhesive components may be used alone or in combination of two or more. Among these adhesive components, polyurethane-based adhesives are preferred.

[0038] The thickness of the adhesive layer 2 is not particularly limited as long as it functions as an adhesive layer, but may be, for example, about 1 to 10 μm, and preferably about 2 to 5 μm.

[0039] [Barrier layer 3] In the packaging material, the barrier layer 3 is a layer that has the function of preventing water vapor, oxygen, light, and the like from penetrating into the inside of the battery in addition to improving the strength of the packaging material. Specific examples of metals constituting the barrier layer 3 include aluminum, stainless steel, and titanium, and preferably aluminum. The barrier layer 3 can be formed, for example, of a metal foil, a metal vapor deposition film, an inorganic oxide vapor deposition film, a carbon-containing inorganic oxide vapor deposition film, or a film provided with these vapor deposition films, and is preferably formed of a metal foil, and more preferably formed of an aluminum alloy foil. From the viewpoint of preventing wrinkles and pinholes from occurring in the barrier layer 3 during the production of the battery packaging material, the barrier layer is more preferably formed of a soft aluminum alloy foil such as annealed aluminum (JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, JIS H4000:2014 A8079P-O).

[0040] The thickness of the barrier layer 3 is not particularly limited as long as it functions as a barrier layer against water vapor, etc., but is preferably about 100 μm or less, more preferably about 10 to 100 μm, and even more preferably about 10 to 80 μm.

[0041] In addition, it is preferable that at least one surface, preferably both surfaces, of the barrier layer 3 are chemically treated in order to stabilize adhesion and prevent dissolution and corrosion. Here, the chemical conversion treatment refers to a treatment for forming an acid-resistant film on the surface of the barrier layer. Examples of the chemical conversion treatment include chromate treatment using a chromium compound such as chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium biphosphate, chromate acetyl acetate, chromium chloride, and potassium chromium sulfate; phosphate treatment using a phosphate compound such as sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphoric acid; and chemical conversion treatment using an aminated phenol polymer having repeating units represented by the following general formulas (1) to (4). In the aminated phenol polymer, the repeating units represented by the following general formulas (1) to (4) may be contained alone or in any combination of two or more types.

[0042] [ka]

[0043] [ka]

[0044] [ka]

[0045] [ka]

[0046] In the general formulas (1) to (4), X represents a hydrogen atom, a hydroxyl group, an alkyl group, a hydroxyalkyl group, an allyl group, or a benzyl group. 1 and R 2 In the general formulae (1) to (4), X and R each may be the same or different and each represents a hydroxyl group, an alkyl group, or a hydroxyalkyl group. 1 and R 2Examples of the alkyl group represented by the formula (I) include linear or branched alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a tert-butyl group. 1 and R 2 Examples of the hydroxyalkyl group represented by the formula (1) include linear or branched alkyl groups having 1 to 4 carbon atoms and substituted with one hydroxy group, such as a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, a 1-hydroxypropyl group, a 2-hydroxypropyl group, a 3-hydroxypropyl group, a 1-hydroxybutyl group, a 2-hydroxybutyl group, a 3-hydroxybutyl group, and a 4-hydroxybutyl group. 1 and R 2 The alkyl group and the hydroxyalkyl group represented by the formulas may be the same or different. In the formulas (1) to (4), X is preferably a hydrogen atom, a hydroxyl group, or a hydroxyalkyl group. The number average molecular weight of the aminated phenol polymer having the repeating units represented by the formulas (1) to (4) is preferably about 500 to 1,000,000, for example, and more preferably about 1,000 to 20,000.

[0047] As a chemical conversion treatment method for imparting corrosion resistance to the barrier layer 3, a method is available in which fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate are dispersed in phosphoric acid, and then baking is performed at 150° C. or higher to form a corrosion-resistant layer on the surface of the barrier layer 3. A resin layer in which a cationic polymer is crosslinked with a crosslinking agent may be further formed on the corrosion-resistant layer. Examples of the cationic polymer include polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine-grafted acrylic resin in which a primary amine is graft-polymerized to an acrylic main skeleton, polyallylamine or a derivative thereof, and aminophenol. These cationic polymers may be used alone or in combination of two or more. Examples of the crosslinking agent include a compound having at least one functional group selected from the group consisting of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent. These crosslinking agents may be used alone or in combination of two or more.

[0048] As a chemical conversion treatment method for imparting corrosion resistance to the barrier layer 3, a method is exemplified in which fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate are dispersed in phosphoric acid, and then baking is performed at 150° C. or higher to form an acid-resistant film on the surface of the barrier layer 3. A resin layer in which a cationic polymer is crosslinked with a crosslinking agent may be further formed on the acid-resistant film. Examples of the cationic polymer include polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine-grafted acrylic resin in which a primary amine is graft-polymerized to an acrylic main skeleton, polyallylamine or a derivative thereof, and aminophenol. These cationic polymers may be used alone or in combination of two or more. Examples of the crosslinking agent include a compound having at least one functional group selected from the group consisting of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent. These crosslinking agents may be used alone or in combination of two or more.

[0049] As a specific method for providing the acid-resistant film, for example, at least the inner layer surface of the aluminum alloy foil is first degreased by a known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then a treatment liquid (aqueous solution) mainly composed of a metal phosphate such as a chromium phosphate, a titanium phosphate, a zirconium phosphate, or a zinc phosphate, or a mixture of these metal salts, or a treatment liquid (aqueous solution) mainly composed of a nonmetallic phosphate and a mixture of these nonmetallic salts, or a treatment liquid (aqueous solution) consisting of a mixture of these and a water-based synthetic resin such as an acrylic resin, a phenolic resin, or a urethane resin, is applied to the degreased surface by a known coating method such as a roll coating method, a gravure printing method, or a dipping method to form an acid-resistant film. For example, treatment with a chromium phosphate-based treatment solution results in an acid-resistant coating made of chromium phosphate, aluminum phosphate, aluminum oxide, aluminum hydroxide, aluminum fluoride, etc., while treatment with a zinc phosphate-based treatment solution results in an acid-resistant coating made of zinc phosphate hydrate, aluminum phosphate, aluminum oxide, aluminum hydroxide, aluminum fluoride, etc.

[0050] As another example of a specific method for providing an acid-resistant coating, for example, at least the inner layer surface of the aluminum alloy foil is first degreased by a well-known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then the degreased surface is subjected to a well-known anodizing treatment to form an acid-resistant coating.

[0051] Other examples of acid-resistant coatings include phosphate-based and chromate-based coatings. Phosphate-based coatings include zinc phosphate, iron phosphate, manganese phosphate, calcium phosphate, and chromium phosphate, while chromate-based coatings include chromium chromate.

[0052] Other examples of acid-resistant coatings include those made of phosphates, chromates, fluorides, triazine thiol compounds, etc., which prevent delamination between the aluminum and the base layer during embossing, prevent dissolution and corrosion of the aluminum surface, particularly aluminum oxide present on the aluminum surface, caused by hydrogen fluoride produced by a reaction between an electrolyte and water, and improve the adhesion (wettability) of the aluminum surface, preventing delamination between the base layer and aluminum during heat sealing, and in the case of embossed types, preventing delamination between the base layer and aluminum during press molding. Among the substances that form acid-resistant coatings, an aqueous solution composed of three components, phenol resin, chromium (III) fluoride compound, and phosphoric acid, is applied to the aluminum surface and then dried and baked.

[0053] The acid-resistant coating may include a layer having cerium oxide, phosphoric acid or a phosphate, an anionic polymer, and a crosslinking agent that crosslinks the anionic polymer, and the phosphoric acid or the phosphate may be blended in an amount of about 1 to 100 parts by mass per 100 parts by mass of the cerium oxide. It is preferable that the acid-resistant coating has a multilayer structure further including a layer having a cationic polymer and a crosslinking agent that crosslinks the cationic polymer.

[0054] Furthermore, the anionic polymer is preferably poly(meth)acrylic acid or a salt thereof, or a copolymer mainly composed of (meth)acrylic acid or a salt thereof.The crosslinking agent is preferably at least one selected from the group consisting of a compound having any one of a functional group of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent.

[0055] The phosphoric acid or the phosphate is preferably a condensed phosphoric acid or a condensed phosphate.

[0056] The chemical conversion treatment may be performed using only one type of chemical conversion treatment, or may be performed using a combination of two or more types of chemical conversion treatment. Furthermore, these chemical conversion treatments may be performed using one type of compound alone, or may be performed using a combination of two or more types of compounds. Among the chemical conversion treatments, chromate treatment and chemical conversion treatments combining a chromium compound, a phosphoric acid compound, and an aminated phenol polymer are preferred. Among the chromium compounds, chromate compounds are preferred.

[0057] Specific examples of the acid-resistant coating include those containing at least one of phosphate, chromate, fluoride, and triazine thiol. Also preferred are acid-resistant coatings containing a cerium compound. As the cerium compound, cerium oxide is preferred.

[0058] Specific examples of the acid-resistant film include a phosphate-based film, a chromate-based film, a fluoride-based film, and a triazine thiol compound film. The acid-resistant film may be one of these films, or a combination of two or more of them. Furthermore, the acid-resistant film may be formed by degreasing the chemically treated surface of the aluminum alloy foil, using a treatment liquid made of a mixture of a metal phosphate and a water-based synthetic resin, or a treatment liquid made of a mixture of a nonmetal phosphate and a water-based synthetic resin.

[0059] The composition of the acid-resistant film can be analyzed, for example, by using time-of-flight secondary ion mass spectrometry. + and Cr + A peak originating from at least one of the above is detected.

[0060] The surface of the aluminum alloy foil is preferably provided with an acid-resistant coating containing at least one element selected from the group consisting of phosphorus, chromium, and cerium. The inclusion of at least one element selected from the group consisting of phosphorus, chromium, and cerium in the acid-resistant coating on the surface of the aluminum alloy foil of the battery packaging material can be confirmed using X-ray photoelectron spectroscopy. Specifically, first, the heat-sealable resin layer, adhesive layer, etc. laminated on the aluminum alloy foil in the battery packaging material are physically peeled off. Next, the aluminum alloy foil is placed in an electric furnace and organic components present on the surface of the aluminum alloy foil are removed at about 300°C for about 30 minutes. Then, the inclusion of these elements is confirmed using X-ray photoelectron spectroscopy of the surface of the aluminum alloy foil.

[0061] The amount of the acid-resistant film formed on the surface of the barrier layer 3 in the chemical conversion treatment is not particularly limited. For example, in the case of the above-mentioned chromate treatment, 2 It is desirable that the chromium compound is contained in an amount of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, calculated as chromium, the phosphorus compound is contained in an amount of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, calculated as phosphorus, and the aminated phenol polymer is contained in an amount of about 1.0 to 200 mg, preferably about 5.0 to 150 mg, calculated as phosphorus, per unit area.

[0062] The thickness of the acid-resistant film is not particularly limited, but is preferably about 1 nm to 10 μm, more preferably about 1 to 100 nm, and even more preferably about 1 to 50 nm, from the viewpoint of the cohesive strength of the film and the adhesive strength with the aluminum alloy foil or the heat-sealing resin layer. The thickness of the acid-resistant film can be measured by observation with a transmission electron microscope, or a combination of observation with a transmission electron microscope and energy dispersive X-ray spectroscopy or electron energy loss spectroscopy.

[0063] The chemical conversion treatment is carried out by applying a solution containing a compound used to form an acid-resistant film to the surface of the barrier layer by a bar coating method, a roll coating method, a gravure coating method, a dipping method, or the like, and then heating the barrier layer so that the temperature of the barrier layer is about 70 to 200° C. In addition, before the chemical conversion treatment is carried out on the barrier layer, the barrier layer may be subjected to a degreasing treatment in advance by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or the like. By carrying out the degreasing treatment in this manner, the chemical conversion treatment of the surface of the barrier layer can be carried out more efficiently.

[0064] [Thermal adhesive resin layer 4] In the packaging material of the present invention, the heat-sealable resin layer 4 corresponds to the innermost layer, and is a layer that seals the battery element by heat-sealing the heat-sealable resin layers together during assembly of the battery.

[0065] The resin component used in the heat-sealable resin layer 4 is not particularly limited as long as it is heat-sealable, and examples thereof include polyolefin, cyclic polyolefin, carboxylic acid-modified polyolefin, and carboxylic acid-modified cyclic polyolefin. That is, the heat-sealable resin layer 4 may contain a polyolefin skeleton, and preferably contains a polyolefin skeleton. The heat-sealable resin layer 4 can be analyzed for its polyolefin skeleton by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, peaks derived from maleic anhydride are detected at wavenumbers of about 1760 cm-1 and about 1780 cm-1. However, if the degree of acid modification is low, the peaks may become small and may not be detected. In that case, it can be analyzed by nuclear magnetic resonance spectroscopy.

[0066] Specific examples of the polyolefin include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); ethylene-butene-propylene terpolymers; etc. Among these polyolefins, polyethylene and polypropylene are preferable.

[0067] The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, butadiene, and isoprene. Examples of the cyclic monomers constituting the cyclic polyolefin include cyclic alkenes such as norbornene; specifically, cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Styrene is also a constituting monomer. Among these polyolefins, cyclic alkenes are preferred, and norbornene is more preferred.

[0068] The carboxylic acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of the polyolefin with a carboxylic acid. Examples of the carboxylic acid used for modification include maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride.

[0069] The carboxylic acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin with an α,β-unsaturated carboxylic acid or its anhydride, or by block-polymerizing or graft-polymerizing an α,β-unsaturated carboxylic acid or its anhydride to the cyclic polyolefin. The cyclic polyolefin to be modified with the carboxylic acid is the same as described above. The carboxylic acid used for the modification is the same as that used for the modification of the carboxylic acid-modified polyolefin.

[0070] Among these resin components, preferred are carboxylic acid-modified polyolefins; more preferred are carboxylic acid-modified polypropylenes.

[0071] The thermally adhesive resin layer 4 may be formed of one type of resin component alone, or may be formed of a blend polymer of two or more types of resin components. Furthermore, the thermally adhesive resin layer 4 may be formed of only one layer, or may be formed of two or more layers of the same or different resin components.

[0072] The thickness of the heat-fusible resin layer 4 can be appropriately selected, but is typically about 10 to 100 μm, and preferably about 15 to 50 μm.

[0073] The heat-sealable resin layer 4 may contain a lubricant, etc., if necessary. When the heat-sealable resin layer 4 contains a lubricant, the moldability of the packaging material can be improved. The lubricant is not particularly limited, and a known lubricant can be used, for example, those exemplified in the above-mentioned base layer 1. The lubricant may be used alone or in combination of two or more. The content of the lubricant in the heat-sealable resin layer 4 is not particularly limited, and from the viewpoint of improving the moldability and insulating property of the electronic packaging material, it is preferably about 0.01 to 0.20 mass %, more preferably about 0.05 to 0.15 mass %.

[0074] [Adhesive layer 5] In the packaging material of the present invention, the adhesive layer 5 is a layer that is optionally provided between the barrier layer 3 and the heat-fusible resin layer 4 in order to firmly bond them together.

[0075] The adhesive layer 5 is formed of a resin capable of bonding the barrier layer 3 and the heat-sealable resin layer 4. The adhesive mechanism, the type of adhesive component, and the like of the adhesive used to form the adhesive layer 5 can be the same as those of the adhesive layer 2. The resin used to form the adhesive layer 5 can also be a polyolefin-based resin such as polyolefin, cyclic polyolefin, carboxylic acid-modified polyolefin, or carboxylic acid-modified cyclic polyolefin exemplified in the heat-sealable resin layer 4. From the viewpoint of excellent adhesion between the barrier layer 3 and the heat-sealable resin layer 4, carboxylic acid-modified polyolefin is preferable as the polyolefin, and carboxylic acid-modified polypropylene is particularly preferable. That is, the adhesive layer 5 may contain a polyolefin skeleton, and preferably contains a polyolefin skeleton. The adhesive layer 5 can be analyzed to contain a polyolefin skeleton by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, maleic anhydride-derived peaks are detected at wave numbers of about 1760 cm-1 and about 1780 cm-1. However, if the degree of acid denaturation is low, the peak may be small and may not be detected. In that case, analysis can be performed using nuclear magnetic resonance spectroscopy.

[0076] Furthermore, from the viewpoint of making the packaging material thin and excellent in impact resistance, it is also preferable that the adhesive layer 5 is a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. As the acid-modified polyolefin, the same carboxylic acid-modified polyolefin and carboxylic acid-modified cyclic polyolefin as exemplified in the heat-sealable resin layer 4 can be preferably exemplified.

[0077] The curing agent is not particularly limited as long as it can cure the acid-modified polyolefin, and examples of the curing agent include epoxy-based curing agents, polyfunctional isocyanate-based curing agents, carbodiimide-based curing agents, and oxazoline-based curing agents.

[0078] The epoxy curing agent is not particularly limited as long as it is a compound having at least one epoxy group. Examples of the epoxy curing agent include epoxy resins such as bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerin polyglycidyl ether, and polyglycerin polyglycidyl ether.

[0079] The polyfunctional isocyanate curing agent is not particularly limited as long as it is a compound having two or more isocyanate groups. Specific examples of the polyfunctional isocyanate curing agent include isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymerized or nurated products thereof, mixtures thereof, and copolymers with other polymers.

[0080] The carbodiimide-based curing agent is not particularly limited as long as it is a compound having at least one carbodiimide group (-N=C=N-). As the carbodiimide-based curing agent, a polycarbodiimide compound having at least two carbodiimide groups is preferable.

[0081] The oxazoline-based curing agent is not particularly limited as long as it is a compound having an oxazoline skeleton, and specific examples of the oxazoline-based curing agent include the EPOCROS series manufactured by Nippon Shokubai Co., Ltd.

[0082] From the viewpoint of improving the adhesion between the barrier layer 3 and the thermally adhesive resin layer 4 by the adhesive layer 5, the curing agent may be composed of two or more kinds of compounds.

[0083] The content of the curing agent in the resin composition forming the adhesive layer 5 is preferably in the range of approximately 0.1 to 50 mass%, more preferably in the range of approximately 0.1 to 30 mass%, and even more preferably in the range of approximately 0.1 to 10 mass%.

[0084] The thickness of the adhesive layer 5 is not particularly limited as long as it functions as an adhesive layer, but when the adhesive layer 2 is used, the thickness is preferably about 2 to 10 μm, more preferably about 2 to 5 μm. When the resin exemplified in the thermal adhesive resin layer 4 is used, the thickness is preferably about 2 to 50 μm, more preferably about 10 to 40 μm. When the adhesive layer 5 is a cured product of an acid-modified polyolefin and a curing agent, the thickness is preferably about 30 μm or less, more preferably about 0.1 to 20 μm, and even more preferably about 0.5 to 5 μm. When the adhesive layer 5 is a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, the adhesive layer 5 can be formed by applying the resin composition and curing it by heating or the like.

[0085] [Surface coating layer] In the packaging material of the present invention, a surface coating layer (not shown) may be provided on the substrate layer 1 (on the side of the substrate layer 1 opposite to the barrier layer 3) as needed for the purpose of improving design, electrolyte resistance, abrasion resistance, formability, etc. The surface coating layer is a layer located on the outermost layer when the battery is assembled.

[0086] The surface coating layer can be formed, for example, from polyvinylidene chloride, polyester resin, urethane resin, acrylic resin, epoxy resin, etc. Among these, the surface coating layer is preferably formed from a two-component curing resin. Examples of the two-component curing resin that forms the surface coating layer include a two-component curing urethane resin, a two-component curing polyester resin, and a two-component curing epoxy resin. In addition, an additive may be blended into the surface coating layer.

[0087] Examples of additives include fine particles having a particle size of about 0.5 nm to 5 μm. The material of the additive is not particularly limited, and examples thereof include metals, metal oxides, inorganic substances, and organic substances. The shape of the additive is also not particularly limited, and examples thereof include spherical, fibrous, plate-like, amorphous, and balloon-like. Specific examples of additives include talc, silica, graphite, kaolin, montmorillonite, montmorillonite, synthetic mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, alumina, carbon black, carbon nanotubes, high melting point nylon, crosslinked acrylic, crosslinked styrene, crosslinked polyethylene, benzoguanamine, gold, aluminum, copper, and nickel. These additives may be used alone or in combination of two or more. Among these additives, silica, barium sulfate, and titanium oxide are preferable from the viewpoints of dispersion stability, cost, etc. Furthermore, the additives may be subjected to various surface treatments such as insulation treatment and high dispersibility treatment.

[0088] The content of the additive in the surface coating layer is not particularly limited, but is preferably about 0.05 to 1.0 mass %, and more preferably about 0.1 to 0.5 mass %.

[0089] The method for forming the surface coating layer is not particularly limited, and may be, for example, a method of applying a two-component curing resin for forming the surface coating layer onto one surface of the base material layer 1. When an additive is added, the additive may be added to the two-component curing resin, mixed, and then applied.

[0090] The thickness of the surface coating layer is not particularly limited as long as it exhibits the above-mentioned functions as a surface coating layer, and is, for example, about 0.5 to 10 μm, preferably about 1 to 5 μm.

[0091] 3. Manufacturing method of packaging materials The method for producing the packaging material of the present invention is not particularly limited as long as a laminate in which each layer of a predetermined composition is laminated can be obtained. An example of the method for producing the packaging material of the present invention is as follows. First, a laminate in which a base layer 1, an adhesive layer 2, and a barrier layer 3 are laminated in this order (hereinafter, sometimes referred to as "laminate A") is formed. Specifically, the formation of the laminate A can be performed by a dry lamination method in which an adhesive used for forming the adhesive layer 2 is applied and dried on the base layer 1 or on the barrier layer 3 whose surface has been chemically treated as necessary, by a coating method such as gravure coating or roll coating, and then the barrier layer 3 or the base layer 1 is laminated and the adhesive layer 2 is cured.

[0092] Next, a heat-fusible resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the heat-fusible resin layer 4 is directly laminated on the barrier layer 3, the resin component constituting the heat-fusible resin layer 4 may be applied on the barrier layer 3 of the laminate A by a method such as gravure coating or roll coating. In addition, in the case of providing the adhesive layer 5 between the barrier layer 3 and the heat-sealable resin layer 4, for example, there can be mentioned (1) a method of laminating the adhesive layer 5 and the heat-sealable resin layer 4 on the barrier layer 3 of the laminate A by co-extruding them (co-extrusion lamination method), (2) a method of separately forming a laminate in which the adhesive layer 5 and the heat-sealable resin layer 4 are laminated, and laminating this on the barrier layer 3 of the laminate A by a thermal lamination method, (3) a method of laminating an adhesive for forming the adhesive layer 5 on the barrier layer 3 of the laminate A by an extrusion method or a method of solution coating, drying at a high temperature, and further baking, and laminating the heat-sealable resin layer 4 previously formed into a sheet-like film on this adhesive layer 5 by a thermal lamination method, and (4) a method of laminating the laminate A and the heat-sealable resin layer 4 via the adhesive layer 5 while pouring a molten adhesive layer 5 between the barrier layer 3 of the laminate A and the heat-sealable resin layer 4 previously formed into a sheet-like film (sandwich lamination method), etc.

[0093] When a surface coating layer is provided, the surface coating layer is laminated on the surface of the base layer 1 opposite to the barrier layer 3. The surface coating layer can be formed, for example, by applying the above-mentioned resin for forming the surface coating layer to the surface of the base layer 1. The order of the step of laminating the barrier layer 3 on the surface of the base layer 1 and the step of laminating the surface coating layer on the surface of the base layer 1 is not particularly limited. For example, after forming the surface coating layer on the surface of the base layer 1, the barrier layer 3 may be formed on the surface of the base layer 1 opposite to the surface coating layer.

[0094] As described above, a laminate is formed which is composed of the surface coating layer (optional), the substrate layer 1, the adhesive layer 2 (optional), the barrier layer 3 whose surface is chemically treated (optional), the adhesive layer 5 (optional), and the heat-sealable resin layer 4. In order to strengthen the adhesiveness of the adhesive layer 2 or the adhesive layer 5, the laminate may be subjected to a heat treatment such as a hot roll contact type, a hot air type, or a near or far infrared type. Conditions for such a heat treatment include, for example, about 150 to 250° C. for about 1 to 5 minutes.

[0095] In the packaging material of the present invention, each layer constituting the laminate may be subjected to a surface activation treatment such as corona treatment, blast treatment, oxidation treatment, ozone treatment, etc., in order to improve or stabilize the film-forming properties, lamination processing, suitability for secondary processing of final products (pouching, embossing), etc.

[0096] 4. Uses of packaging materials The packaging material of the present invention is used in a wide range of fields as a package (a packaging material molded to be able to contain contents) for containing food, medicine, battery elements, etc. When the package of the present invention is used to contain contents such as food, medicine, battery elements, etc., the sealant part of the package is used so as to face inside (the surface in contact with the contents).

[0097] For example, when the packaging material of the present invention is used as a packaging material for a battery, a battery element having at least a positive electrode, a negative electrode, and an electrolyte is covered with a package formed from the packaging material of the present invention in a state in which metal terminals connected to each of the positive electrode and negative electrode protrude outward, so that a flange portion (a region where the heat-sealable resin layers come into contact with each other) can be formed around the periphery of the battery element, and the heat-sealable resin layers of the flange portion are heat-sealed to seal the same, thereby providing a battery in which the battery element is accommodated in the package.

[0098] The battery packaging material of the present invention may be used for either primary or secondary batteries, but is preferably used for secondary batteries. The type of secondary battery is not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, lead storage batteries, nickel-hydrogen storage batteries, nickel-cadmium storage batteries, nickel-iron storage batteries, nickel-zinc storage batteries, silver oxide-zinc storage batteries, metal-air batteries, polyvalent cation batteries, condensers, and capacitors. Among these secondary batteries, lithium ion batteries and lithium ion polymer batteries are suitable applications of the battery packaging material. EXAMPLES

[0099] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0100] Examples 1-5 and Comparative Examples 1-4 <Production of packaging materials> In each case, a barrier layer made of aluminum foil (JIS H4160:1994 A8021H-O) that had been chemically treated on both sides was laminated on the substrate layer by dry lamination. Specifically, a two-liquid urethane adhesive (a polyol compound and an aromatic isocyanate compound) was applied to one side of the barrier layer to form an adhesive layer (thickness 3 μm) on the barrier layer. Next, the adhesive layer on the barrier layer and the substrate layer were laminated, and an aging treatment was performed to produce a substrate layer / adhesive layer / barrier layer laminate. The chemical conversion treatment of the aluminum foil used as the barrier layer was performed using a treatment solution consisting of a phenolic resin, a chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m. 2 (dry weight) was applied to both sides of an aluminum foil by roll coating, and then baked.

[0101] Next, in Examples 1, 2, and 5 and Comparative Examples 1 and 2, a carboxylic acid-modified polypropylene (placed on the barrier layer side) and a random polypropylene (innermost layer) were co-extruded on the barrier layer of the laminate to laminate an adhesive layer / thermal adhesive resin layer on the barrier layer. Next, the obtained laminate was heated to obtain a packaging material in which a base layer, an adhesive layer, a barrier layer, an adhesive layer, and a thermal adhesive resin layer were laminated in this order. In the base layer used in Example 5, the PET (thickness 12 μm) and the nylon (thickness 15 μm) were bonded with a two-liquid urethane adhesive (thickness 3 μm).

[0102] On the other hand, in Examples 3 and 4 and Comparative Examples 3 and 4, a solution obtained by mixing carboxylic acid-modified polypropylene and an epoxy-based curing agent was applied onto the barrier layer of the laminate and dried. An unstretched polypropylene film (innermost layer) was further laminated thereon. The content of the curing agent was 5% by mass relative to the total solid mass after drying. Next, the obtained laminate was aged to obtain a packaging material in which a base layer, an adhesive layer, a barrier layer, an adhesive layer, and a heat-sealable resin layer were laminated in this order.

[0103] The laminated structure and the thickness of each layer in each of the examples and comparative examples are as follows. Example 1: Nylon (25 μm) / adhesive layer (3 μm) / aluminum foil (40 μm) / carboxylic acid modified polypropylene (23 μm) / polypropylene (23 μm) Example 2: Nylon (25 μm) / adhesive layer (3 μm) / aluminum foil (25 μm) / carboxylic acid modified polypropylene (14 μm) / polypropylene (10 μm) Example 3: Nylon (25 μm) / adhesive layer (3 μm) / aluminum foil (25 μm) / cured product of carboxylic acid-modified polypropylene and curing agent (2 μm) / unstretched polypropylene (25 μm) Example 4: Nylon (25 μm) / adhesive layer (3 μm) / aluminum foil (35 μm) / cured product of carboxylic acid-modified polypropylene and curing agent (2 μm) / unstretched polypropylene (30 μm) Example 5: PET (12 μm) / adhesive (3 μm) / nylon (15 μm) / adhesive layer (3 μm) / aluminum foil (40 μm) / carboxylic acid modified polypropylene (40 μm) / polypropylene (40 μm)

[0104] Comparative Example 1: PET (12 μm) / adhesive layer (3 μm) / aluminum foil (25 μm) / carboxylic acid-modified polypropylene (14 μm) / polypropylene (10 μm) Comparative Example 2: Nylon (15 μm) / adhesive layer (3 μm) / aluminum foil (35 μm) / carboxylic acid-modified polypropylene (20 μm) / polypropylene (15 μm) Comparative Example 3: PET (12 μm) / adhesive layer (3 μm) / aluminum foil (25 μm) / cured product of carboxylic acid-modified polypropylene and curing agent (2 μm) / unstretched polypropylene (25 μm) Comparative Example 4: Nylon (15 μm) / adhesive layer (3 μm) / aluminum foil (35 μm) / cured product of carboxylic acid-modified polypropylene and curing agent (2 μm) / unstretched polypropylene (30 μm)

[0105] <Break energy of laminate> For each of the packaging materials obtained above, the breaking energy per 1 m of unit width in MD and TD was calculated by obtaining data on the "test force-displacement curve" measured when performing a tensile test under the following test conditions for the MD and TD of each packaging material, saving the data in a csv file format, and integrating the data until the laminate broke using a spreadsheet software (Microsoft Excel (registered trademark)). At this time, the breaking energy per 1 m of width of each packaging material was converted (divided by 0.015) using the spreadsheet software and calculated. Then, the breaking energy per 1 m of unit width in MD and the breaking energy per 1 m of unit width in TD were summed up. Five packaging materials were prepared for each measurement, and the average of the three breaking energy values ​​for the five samples, excluding the maximum and minimum values, was taken as the breaking energy of the laminate. The results are shown in Table 1. (Test conditions) Test speed: 50mm / min Specimen width: 15mm Specimen length: 100mm ·Gage distance: 30mm

[0106] For reference, Fig. 4 shows the test force-displacement curve obtained in the tensile test (MD) of the packaging material of Comparative Example 2. The portion obtained by integrating the data of the test force-displacement curve is the integral value from the start of the tensile test (displacement 0) to the breaking point P of the laminate, as shown in the schematic diagram of Fig. 5, for example, and corresponds to the area of ​​the shaded portion in Fig. 5.

[0107] <Puncture strength of laminate> The puncture strength of each of the packaging materials obtained above was measured from the base layer side according to the method specified in JIS Z1707:1995. The puncture strength was measured using Imada's ZP-50N (force gauge) and MX2-500N (measurement stand). The results are shown in Table 1.

[0108] <Total penetration energy of laminate> For each of the packaging materials obtained above, the total penetration energy was measured from the base layer side by a method conforming to the provisions of JIS K7124-2:1999. The measurement device used was a drop-weight type graphic impact tester (manufactured by Toyo Seiki Co., Ltd.). The measurement conditions were as follows: hammer weight 6.4 kg, drop height 300 mm, sample clamp diameter 40 mmφ, hammer diameter 12.7 mmφ, and hammer shape hemispherical. The results are shown in Table 1.

[0109] <Puncture strength of each layer> The substrate layer, barrier layer, and further laminates of the adhesive layer and heat-sealable resin layer used in the manufacture of the above packaging material were prepared, and the puncture strength of each was measured from the substrate layer side by a method conforming to the provisions of JIS Z1707:1995. The puncture strength was measured using Imada's ZP-50N (force gauge) and MX2-500N (measurement stand). The results are shown in Table 1.

[0110] <Impact resistance evaluation of packaging materials> Each packaging material obtained above was cut to 90 mm x 150 mm, and then cold molded to a depth of 3.0 mm at 0.9 MPa using a molding die (female die) with a diameter of 32 mm x 55 mm and a corresponding molding die (male die), forming a recess in the center. A PET resin with a width of 30 mm, length of 52 mm, and thickness of 3 mm was placed in this recess as a pseudo battery element. Next, the unmolded part of the molded product was folded so that the sealant surface faced each other, and the peripheral part was heat-sealed to prepare a pseudo battery. The heat sealing conditions were 190°C, surface pressure of 1.0 MPa, and 3 seconds.

[0111] Next, the molded product was placed on a rigid, flat surface, and a 16 mm diameter round bar was placed in the center of the molded product so that it crossed the molded product. Next, a 9.1 kg weight was dropped onto the round bar from a height of 610 mm. After the drop, molded products that were not broken were evaluated as having excellent impact resistance (A), and those that were broken were evaluated as having poor impact resistance (C). The results are shown in Table 1.

[0112] [Table 1]

[0113] As is clear from the results shown in Table 1, the packaging materials of Examples 1 to 5, in which the breaking energy per unit width of 1 m calculated from the test force-displacement curve measured when a tensile test was performed under the above test conditions is 400 J or more in total in one direction (MD) perpendicular to the thickness direction of the laminate and in the other direction (TD) perpendicular to both the one direction and the thickness direction of the laminate, have excellent impact resistance. On the other hand, the packaging materials of Comparative Examples 1 to 4, in which the total breaking energy is less than 400 J, have inferior impact resistance compared to Examples 1 to 5. [Explanation of symbols]

[0114] 1 Base material layer 2 Adhesive layer 3. Barrier layer 4 Heat-fusible resin layer 5 Adhesive layer

Claims

1. The laminate includes at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The thickness of the base layer is 75 μm or less, The barrier layer has a thickness of 100 μm or less, The thickness of the heat-sealing resin layer is 100 μm or less, The laminate has a breaking energy per meter of unit width calculated from a test force-displacement curve measured when a tensile test is performed under the following test conditions, and the breaking energy per meter of unit width is 400 J or more in total in one direction perpendicular to the thickness direction of the laminate and in another direction perpendicular to both the one direction and the thickness direction of the laminate. (Test conditions) Test speed: 50 mm / min Test piece width: 15 mm Length of test piece: 100 mm Gauge distance: 30mm

2. The battery packaging material according to claim 1 , wherein the heat-sealable resin layer is formed of two or more layers made of the same or different resin components.

3. The battery packaging material according to claim 1 , wherein a lubricant is present on at least one of the surface and the interior of the base material layer.

4. The battery packaging material according to claim 1 or 2, wherein two or more types of lubricants are present on at least one of the surface and the interior of the base material layer.

5. The battery packaging material according to any one of claims 1 to 4, wherein a lubricant is present on at least one of the surface and the interior of the heat-sealable resin layer.

6. The battery packaging material according to any one of claims 1 to 4, wherein two or more types of lubricants are present on at least one of the surface and the interior of the heat-sealable resin layer.

7. The battery packaging material according to any one of claims 1 to 6, wherein the one direction is the MD of the laminate, and the other direction is the TD of the laminate.

8. The laminate has a puncture strength of 23 N or more measured from the base layer side by a method conforming to the provisions of JIS Z1707:1995. The battery packaging material according to any one of claims 1 to 7.

9. The laminate has a total penetration energy of 1.4 J or more measured from the base layer side in accordance with the provisions of JIS K7124-2:1999 under the following measurement conditions. The battery packaging material according to any one of claims 1 to 8. (Measurement conditions) Hammer weight: 6.4kg Drop height: 300mm Sample clamp diameter: 40 mm Hammer diameter: 12.7 mm Hammer shape: Hemispherical

10. The battery packaging material according to any one of claims 1 to 9, wherein the substrate layer has a thickness of 20 µm or more.

11. The battery packaging material according to any one of claims 1 to 10, wherein the barrier layer is composed of at least one metal foil selected from the group consisting of aluminum alloy, stainless steel, and titanium.

12. The battery packaging material according to any one of claims 1 to 11, wherein the base layer has a multilayer structure in which a polyester film and a nylon film are laminated, a multilayer structure in which a plurality of nylon films are laminated, or a multilayer structure in which a plurality of polyester films are laminated.

13. The battery packaging material according to any one of claims 1 to 12, wherein two or more types of lubricants are present on at least one of the surface and the interior of the base material layer.

14. The thickness of the barrier layer is 40 μm or less, Alternatively, the battery packaging material according to any one of claims 1 to 13, wherein the barrier layer has a thickness of more than 40 µm and not more than 100 µm.

15. The battery packaging material according to any one of claims 1 to 14, wherein the heat-sealable resin layer is composed of a resin containing a polyolefin skeleton.

16. The battery packaging material according to any one of claims 1 to 15, wherein the heat-sealable resin layer contains at least one selected from the group consisting of polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins.

17. The battery packaging material according to any one of claims 1 to 16, wherein the heat-sealable resin layer is formed from a blend polymer of two or more types of resin.

18. The battery packaging material according to any one of claims 1 to 17, wherein the heat-sealable resin layer is formed of two or more layers made of the same or different resin components.

19. The battery packaging material according to any one of claims 1 to 18, wherein two or more types of lubricants are present on at least one of the surface and the interior of the heat-sealable resin layer.

20. The battery packaging material according to any one of claims 1 to 19, wherein at least two selected from the group consisting of saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides are present on at least one of the surface and the interior of the heat-sealable resin layer.

21. The battery packaging material according to any one of claims 1 to 20, which is used for housing a battery element.

22. A battery, comprising a battery element including at least a positive electrode, a negative electrode, and an electrolyte, housed in a package formed from the battery packaging material according to any one of claims 1 to 21.

23. The method includes a step of obtaining a battery packaging material composed of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, The thickness of the base layer is 75 μm or less, The barrier layer has a thickness of 100 μm or less, The thickness of the heat-sealing resin layer is 100 μm or less, The laminate has a breaking energy per meter of unit width calculated from a test force-displacement curve measured when a tensile test is performed under the following test conditions, and the breaking energy per meter of unit width is 400 J or more in total in one direction perpendicular to the thickness direction of the laminate and in another direction perpendicular to both the one direction and the thickness direction of the laminate. (Test conditions) Test speed: 50 mm / min Test piece width: 15 mm Length of test piece: 100 mm Gauge distance: 30mm

24. An adhesive layer is provided between the barrier layer and the thermal adhesive resin layer, 24. The method for producing a battery packaging material according to claim 23, wherein the adhesive layer and the heat-sealable resin layer are formed by a co-extrusion lamination method, a thermal lamination method, a method of laminating an adhesive for forming the adhesive layer on the barrier layer and laminating the heat-sealable resin layer, which has been formed in advance into a sheet shape, on the adhesive layer, or a sandwich lamination method.

25. An adhesive layer is provided between the barrier layer and the thermal adhesive resin layer, The method for producing a battery packaging material according to claim 23 or 24, wherein the heat-sealable resin layer is formed of two or more layers made of the same or different resin components.

Citation Information

Patent Citations

  • Method of manufacturing packing material such as battery case

    JP2005026152A

  • Paper bag

    JP2005145561A

  • Layered package material, outer package material for battery, and the battery

    JP2008287971A

  • Primer, electroconductor foil with resin, laminated plate and method of producing laminated plate

    JP2009132929A

  • Thermosetting type die bond film, dicing-die bond film and semiconductor device

    JP2011060848A